Glioblastoma multiforme or brain abscess - Shrestha, P; Pant, B (Journal of Institute of Medicine Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> It is not uncommon for brain abscess and glioblastoma multiforme (GBM) to be confused with one another in neuroimagings. Due to preoperative diagnostic dilemma, treatment strategy and prognosis cannot be explained in advance. In this context, we present a case of 50 year-old male patient with features of raised intracranial pressure (ICP) and left hemiparesis. His computed tomographic (CT) scan and magnetic resonance imaging (MRI) of head showed central cystic lesion with ring enhancement with significant perifocal edema. Provisional diagnosis of GBM was made. Surgery was performed with craniotomy. Intraoperative picture showed a cystic lesion with thick capsule containing pus. Histological report showed plenty of inflammatory cells without any evidence of GBM. There are various neuroimaging techniques to differentiate brain abscess from GBM. However, in Nepalese context, they are hardly applicable. By this article, we intend to emphasize that brain abscess and GBM are very difficult to differentiate and thus thorough evaluation is needed before surgery is contemplated so as to make an appropriate treatment plan. Key words: brain abscess, GBM, neuroimaging technique The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 23-25